The Te Deum in Cyrillic Transcription with a Church Slavonic Interlinear Translation - Springfield Tomelleri, Vittorio (Slavistica Vilnensis, 2023)
The Latin Psalter from the Chudov monastery, written in Cyrillic letters around the end of the 15th century, is a document of paramount importance for the study of the Latin cultural tradition in Muscovy. This unique manuscript seems to be linked to the fervent translation activity directed by the archbishop of Novgorod Gennadii (1484–1504). The wide space left between the lines of the main Latin text was without doubt supposed to be filled with the Church Slavic corresponding text. A Slavic “translation” was indeed inserted into the biblical cantica and other texts, among which the hymn Te Deum, traditionally (and wrongly) considered to be a joint composition by Saint Ambrose and Saint Augustine, which was very widespread in the Western Church.The article features the first diplomatic interlinear edition of the Slavic-Latin Te Deum, which is preceded by a short description and analysis of the Slavic text and its main linguistic peculiarities in comparison with another translation of the same work, made some decades later by Dmitry Gerasimov. Here all relevant differences between the two Slavic versions, both at the lexical and grammatical levels, are presented and shortly discussed. Further, some evident errors in the Slavic text of the Chudov Psalter cast some doubts on the possibility to consider it a real translation in the strict sense of the term; it seems rather to function as a lexico-grammatical interlinear gloss, to be read vertically as an auxiliary tool for a proper understanding of the Latin original.